Hubungan Kausalitas Produk Dsomestik Regional Bruto, Indeks Pembangunan Manusia dan Kemiskinan di Indonesia - Akbar, Aldi Maulana; aji, tony seno (Jurnal Ekonomika : INDEPENDEN, 2023)
This research aims to determine the causal relationships among variables. The variables used in this study include Gross Regional Domestic Product (GRDP), the Human Development Index (HDI), and poverty in Indonesia. This research uses a quantitative approach. The research methods used are Granger causality. The results of this study show that there is causal one way relationship between HDI and poverty, there is a causal two way relationship between HDI and GRDP, and there is a causal two way relationship between poverty and GRDP.